2019
DOI: 10.2196/10350
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Acceptability of Text Messaging for Diabetes Care in Primary Care in Argentina: Exploratory Study

Abstract: Background Engagement in self-care behaviors that are essential to optimize diabetes care is challenging for many patients with diabetes. mHealth interventions have been shown to be effective in improving health care outcomes in diabetes. However, more research is needed on patient perceptions to support these interventions, especially in resource settings in low- and middle-income countries. Objective The goal of the research was to explore perceptions and acceptabilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 43 publications
1
18
0
1
Order By: Relevance
“…Our findings also differ somewhat from other prior qualitative studies of text messaging, as our participants placed less emphasis on texts that invoke social concepts. A qualitative interview study in Argentina found that patients appreciated socially framed content in text messages [38], a finding consistent with survey data showing modestly high preferences for texts incorporating social support [21]. These differences could be attributable to culture or preferences for social support across different countries and populations, possibly because culture in the United States is generally more individualistic [39][40][41][42].…”
Section: Comparison With Prior Worksupporting
confidence: 53%
“…Our findings also differ somewhat from other prior qualitative studies of text messaging, as our participants placed less emphasis on texts that invoke social concepts. A qualitative interview study in Argentina found that patients appreciated socially framed content in text messages [38], a finding consistent with survey data showing modestly high preferences for texts incorporating social support [21]. These differences could be attributable to culture or preferences for social support across different countries and populations, possibly because culture in the United States is generally more individualistic [39][40][41][42].…”
Section: Comparison With Prior Worksupporting
confidence: 53%
“…Following the HBM, sending an SMS would work as a cue to promote actions and therefore prompt HPV-positive women to undergo Pap triage. In this sense, the SMS must address beliefs, values, and shared perceptions to encourage the prevention behavior [31,46,47].…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…However, a non-significant increase (7.44 at baseline to 7.55 after 10 months; P value 0.210) was reported in the study [35]. In another study, Moyano, D., et al, assessed the perceptions and acceptability of SMS text messaging for diabetes care in a primary care setting in Argentina by using a 24-semi-structured questions, and showed that SMS-has a positive contribution in the care of individuals with diabetes [36]. A separate pilot study by Dobson R., et al, evaluated the ability of Self-Management Support for Blood Glucose (SMS4BG), a tailored text message-based intervention, among adults with uncontrolled diabetes.…”
Section: Plos Onementioning
confidence: 84%